The structure of the human mitochondrial ribosome - Amunts, Alexey (Science, 2015)
The highly divergent ribosomes of human mitochondria (mitoribosomes) synthesize 13 essential proteins of oxidative phosphorylation complexes. We have determined the structure of the intact mitoribosome to 3.5 angstrom resolution by single-particle electron cryo-microscopy. It reveals 80 extensively interconnected proteins, 36 of which are specific to mitochondria, and three rRNA molecules. The head domain of the small subunit, particularly the mRNA channel, is highly remodeled. Many intersubunit bridges are unique to the mitoribosome, which adopts conformations involving ratcheting or rolling of the small subunit that are distinct from those seen in bacteria or eukaryotes. An intrinsic GTPase mediates a contact between the head and central protuberance. The structure provides a reference for analysis of mutations that cause severe pathologies, and for future drug design.